Simulation Study of Direct-Shear Test on FRP-to-Concrete Bonded Joints by Means of XFEM - Jankowiak, Iwona (Engineering Transactions, 2025)
A proper numerical modelling of FRP-to-concrete bonded joints is crucial for determining their strength. In this paper the results of numerical analyses performed by XFEM on such joints in direct-shear test are presented. The study uses a fracture mechanics approach based on the traction-separation law for definition the FRP-concrete interface. It includes definition of damage initiation as well as damage evolution, taking advantage of the fracture energy for plain concrete as well as the interfacial fracture energy of analysed joint. The interfacial fracture energy of bonded joint is essential for accurately describing the local bond–slip behaviour. The numerical study is aimed to investigate the sensitivity of direct-shear test models to magnitude of fracture energies, material strengths, type of adhesive and the length of FRP-to-concrete joint. Some general results and conclusions of performed analyses are presented.